Use of Geostatistics in the sugarcane context in Brazil: a review - Cardoso, Luiz Antonio Soares; Silva Farias, Paulo Roberto; Soares, João Almiro Corrêa; de Oliveira, Fábio Júnior (Environment, development and sustainability, 2025)
The use of Geostatistics has become increasingly popular in recent decades in the context of agricultural sciences, representing an excellent innovation tool for rural producers and researchers who develop work in the most diverse agricultural cultures. This popularization is justified due to the optimization that Geostatistics brings to the production process, reducing unnecessary expenses on the part of the producer and mitigating negative impacts of agricultural activity on the environment. In this scenario, this article seeks to emphasize the use of Geostatistics in the context of sugarcane culture in Brazil, which represents the third largest agricultural crop with planted area in the country, seeking, through a systematic review, to highlight the importance of Geostatistics as a Precision Agriculture tool for this crop. To achieve this objective, we developed a systematic survey in important indexing bases of national and international scientific works, which made it possible to identify published works on the subject in Brazil, allowing the visualization of the regions where this innovative tool is being used. At the end of the review, it was possible to measure the current state of research with Geostatistics developed in sugarcane plantations throughout the Brazilian territory, which allowed us to conclude that there is a heterogeneity in the distribution of these researches, which can be explained by legal restrictions for the development of the culture in certain regions or the lack of better dissemination of research through journals with greater impact.